ANALYSIS OF LOGISTICS AND SUPPLY CHAIN MANAGEMENT AGILITY IN CORRUGATED BOX INDUSTRY - Yosef Daryanto; Klaus KrÃ¤mer (Spektrum Industri, 2016)
Several analyses were performed in this case study including the analysis of the business environmentsand the current supply chain system, which than followed by measurement and comparison of supplychain agility performance indicator. As corrugated box industry work in make/engineer to order systemand by considering their competitive situation and uncertain business environment it was concluded thatthey need agility in their supply chain. The main problem was the unbalance power position with papersupplier that resulting low inbound inventory turns. Focusing on this weakness, two solutions wereproposed; those are building higher collaboration with paper suppliers and performing better inventorymanagement by set different inventory control and policy for each inventory class. Keywords: Corrugated box industry, performance indicator, supply chain agility.